2015
DOI: 10.1002/prp2.144
|View full text |Cite
|
Sign up to set email alerts
|

TRO40303, a mitochondrial‐targeted cytoprotective compound, provides protection in hepatitis models

Abstract: TRO40303 is cytoprotective compound that was shown to reduce infarct size in preclinical models of myocardial infarction. It targets mitochondria, delays mitochondrial permeability transition pore (mPTP) opening and reduces oxidative stress in cardiomyocytes submitted to ischemia/reperfusion in vitro. Because the involvement of the mitochondria and the mPTP has been demonstrated in chronic as well as acute hepatitis, we investigated the potential of TRO40303 to prevent hepatocyte injury. A first set of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Acute liver injury is a major public health problem worldwide that arises from various etiologies including viral hepatitis, drug or alcohol‐induced injury, as well as hepatic ischemia‐reperfusion injury (Schaller et al, ). d ‐Galactosamine (GalN) induces liver cell injury in rodents, which closely resembles human acute viral hepatitis in its morphological and functional features (Keppler & Decker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute liver injury is a major public health problem worldwide that arises from various etiologies including viral hepatitis, drug or alcohol‐induced injury, as well as hepatic ischemia‐reperfusion injury (Schaller et al, ). d ‐Galactosamine (GalN) induces liver cell injury in rodents, which closely resembles human acute viral hepatitis in its morphological and functional features (Keppler & Decker, ).…”
Section: Introductionmentioning
confidence: 99%
“…A sublethal dose of TRO40303 has also been tested in an experimental hepatitis model where the authors showed a significant reduction in mortality [45]. The dose chosen in the MITOCARE trial might have been inadequate to achieve the optimal delaying of the mPTP opening and higher dosage could be essential in order to reduce oxidative stress in the ischemic reperfused cardiomyocytes more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The opening of mPTP can be modulated directly by different pharmacologic agents, for example, cyclosporine or indirectly for instance by preconditioning [44]. In vitro studies have shown that the blockage of the mPTP in ischemic cardiomyocytes resulted in reduced levels of oxidative stress [45]. So far, 5 randomized trials have investigated the effect of cyclosporine on reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…As a MPTP inhibitor, TRO40303 can effectively maintain the cell membrane potential and prevent necrosis in animal models of alcoholic pancreatitis and human acinar cells (39). TRO40303 is effective and well tolerated in the treatment of acute myocardial infarction and hepatitis and may be an effective way to treat AP (40,41). A multicenter clinical trial is underway to evaluate the effectiveness of high-calorie parenteral nutrition (PN) to maintain sufficient ATP consumption during AP (42).…”
Section: Ca 2+ Signaling and Mitochondrial Dysfunctionmentioning
confidence: 99%